Investigations on Grid-Connected DFIWGs Development and Performance Analysis with the Support of Crowbar and STATCOM - Mahmoud, Mohamed Metwally; Benlaloui, Idriss; Benbouya, Basma; Ibrahim, Nagwa F. (Peneliti Teknologi Teknik Indonesia, 2024)
These days, one of the most used layouts in the wind power industry is a variable-speed doubly-fed induction wind generator (DFIWG). To provide real and reactive power (PQ) control during grid failures, this research examines the DFIWG. The system's transient behavior is examined under normal and abnormal conditions. Through rotor side converter (RSC) and grid side converter (GSC) control, Q assistance for the grid, and power converter stress reduction, the suggested control approach achieves system stability while enabling DFIWG to operate smoothly during grid failures. By suppressing rotor and stator overcurrent, DC link voltage (VDC) overshoot, and PQ oscillations, as well as supporting the grid voltage (GV) under both balanced and unbalanced grid fault scenarios with distinct voltage dips, the suggested technique preserves the system characteristics during grid faults. MATLAB/SIMULINK 2017b is used for time-domain computer simulations. STATCOM and crowbar, two suggested systems, are contrasted. This work proves the effectiveness of the suggested approaches in augmenting the system's fault ride-through (FRT) capacity.